Tax Agressiveness in Family Firms: Can Corporate Governance Mitigate It? - Arie Pratama (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2021)
Every taxpayers objectives is to minimize the tax paid to government. Few business tried to avoid tax more agressively than the others. This research will tried to investigate whether the family firms are more tax agressive compare to non family firms. Tax agressiveness might be reduced if there is a working governance structure. This research will also investigate whether the governance structure (i.e size of board of director, proportion of independent director, external audit firms, and audit committee) would significantly reduced the tax agressiveness. To control the results, researcher used size, profitability and leverage. This research was quantitative explanatory research. Researcher will analyzed 15 out of 57 family own-business in Indonesia, and make a comparison with non family firms. Researcher examined the financial statements and annual report from year 2011 – 2015. The research will used multiple regression analysis as a data analysis tools. This research will produce tax agressiveness analysis of family firms, non family firms, and combination of both firms. The research showed that, contrast to the non family firms, family firms had agressive tax avoidance scheme. The research also showed that corporate governance in family company in fact, increasing the agressiveness o tax avoidance, while non family firms corporate governance reduced the agressiveness of tax avoidance. Overall this research showed that family business need to improve the governance structure to control its agressive tax avoidance. Keywords: Corporate Governance, Family Business, Ownership, Tax Avoidance.